Religiusitas: Faktor Protektif Pengasuhan Orangtua dengan Status Sosial Ekonomi Rendah - Diany Ufieta Syafitri; M. Noor Rochman Hadjam (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2017)
The low family socioeconomic status (SES) often resulted in variety of negative impact towards child development. One of the mechanism how SES affect children is through parenting. In family with low SES, many parents experience stress due to economic pressure that they implement harsh parenting practices. This then leads to various negative impact in children psychological development. One of the most significant protective factor to reduce the negative impact of low SES is religiosity. Based on thedimensions of religiosity, this research tried to capture how religiosity among low SES parents can serve as protective factor. The subjects of this research three low SES parents who considered as religios by local people and their children managed to achieve high education. The research method is quallitative with in-depth interview. The data analysis employed by coding, formulating units of meaning, and categorization. The results showed that based on the five dimensions of religiosity, all three subjects have adequate religious knowledge particularly related to religionbasedparenting knowledge, then this followed by intensive and devoted religiousritual, and from experiential dimension they often experience grace and closeness to Allah SWT. The impact of those five dimensions of religiosity is they are able to show many positive virtues which enables them to overcome various obstacles the low SES brought. Those virtues are patience, sincere, nrimo (acceptance), pasrah (surrender), and optimistic. They also then transmitted their religiosity to their children with valueinternalization and  guiding worship rituals. Keywords: low soscioeconomic status, parenting, protective factor, positive virtues, religosity